Chromium (VI) Removal Methods from Effluents – A Review Article (University of Khartoum Engineering Journal, 2021)
Heavy metal is one of the major environmental and ecological problems in this world. The presence of heavy metals in water andwastewater causes toxic effects to the living beings and the environment. Compared to other heavy metals (such as Cr6+, Pb2+, Zn2+ etc.,) the presence of chromium in industrial effluents has become a major problem worldwide as hexavalent chromium is highly toxic to animals due to its ability to generate reactive oxygen species in cells. The excess amount of chromium affects the lungs and lead to respiratory disorders in the human beings. It also contaminates the soil and groundwater. Due to a large number of industries that generate hexavalent chromium in its effluents such as tanneries and electroplating industries, the chromium contamination in the wastewater and aqueous solutions exceeds the tolerance limits. Many remediation processes for removal of hexavalent chromium have been researched and reviewed extensively. Many methods are used to remove the chromium from the aqueous solutions and industrial effluents. This paper reviewed different remediation methods namely: the using of natural absorbent; the conventional chemical reduction method; the bio-absorbent method, nano-technology application; and other remediation methods. For each method, information about major parameters affecting theefficiency of removal of hexavalent chromium (Cr6+) from industrial effluent are stated. Brief discussion is included relating the different methods, in addition to some future aspects for the remediation process.